Study the Applicability of a Shelf-Type Fish Drying Machine with a Heat Source from Coconut Shell Biomass - Budi, Agus Sulistiyo; Bakhri, Mohammad Samsul; Nurasri, Yuli; Suripto, Aghna Ilma Nurdin; Amir, Sultan Krisna; Rojikin, Rojikin (Universitas Muhammadiyah Yogyakarta, 2023)
The sun’s heat is usually utilized to dry traditional processed salted fish. However, its quality suffers as a result of the lengthy drying process. This issue can only be resolved with the help of efficient drying equipment. Advantages of artificial drying include selecting the drying capacity according to requirements, without requiring a considerable space, and managing the drying conditions. This research aims to discover an effective way to utilize biomass waste from coconut shells to speed up the drying process for salted fish. The study method involved several steps: acquiring data, analyzing the tools and machine, observing the machine, and designing a new machine. The three airspeed parameters tested in this study were 7 m/s, 10 m/s, and 12 m/s. The drying shelf reached a maximum temperature of 81.4 °C at 7 m/s, 100.3 °C at 10 m/s, and 99.4 °C at 12 m/s.